2020
DOI: 10.1002/mbo3.1006
|View full text |Cite
|
Sign up to set email alerts
|

A novel way to synthesize pantothenate in bacteria involves β‐alanine synthase present in uracil degradation pathway

Abstract: Pantothenate is an indispensable vitamin precursor of the synthesis of coenzyme A (CoA), a key metabolite required in over 100 metabolic reactions. β‐Alanine (β‐ala) is an indispensable component of pantothenate. Due to the metabolic relevance of this pathway, we assumed that orthologous genes for ß‐alanine synthesis would be present in the genomes of bacteria, archaea, and eukaryotes. However, comparative genomic studies revealed that orthologous gene replacement and loss of synteny occur at high frequency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
(48 reference statements)
0
19
0
Order By: Relevance
“…Another differential metabolite in the OPC group was dihydrouracil related to beta-alanine metabolism, pantothenate and CoA biosynthesis, and pyrimidine metabolism. Dihydrouracil is an intermediate breakdown product from pyrimidine metabolism in the liver; it could be transformed into beta-alanine and then into malonyl CoA by transamination to participate in beta-alanine metabolism and pantothenate and CoA biosynthesis (López-Sámano et al, 2020). Beta-alanine is also one of the pantothenic acid ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…Another differential metabolite in the OPC group was dihydrouracil related to beta-alanine metabolism, pantothenate and CoA biosynthesis, and pyrimidine metabolism. Dihydrouracil is an intermediate breakdown product from pyrimidine metabolism in the liver; it could be transformed into beta-alanine and then into malonyl CoA by transamination to participate in beta-alanine metabolism and pantothenate and CoA biosynthesis (López-Sámano et al, 2020). Beta-alanine is also one of the pantothenic acid ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…UDP and UTP regulate the activity of animal carbamoyl phosphate synthase II, and uracil is also involved in the biosynthesis of polysaccharides and the transport of aldose‐containing sugars. 46 Therefore, the significant increases in the serum level of uracil observed in this study suggest that many biochemical reactions in the experimental group were triggered, possibly owing to metabolic disorders, and increased cellular oxidative stress. These results were inconsistent with those of previous studies, which showed decreases in serum concentration of uracil in patients with both coronary artery disease and MetS.…”
Section: Discussionmentioning
confidence: 63%
“…In Rhizobium etli CFN42, β-alanine is synthesized from the reductive pyrimidine degradation pathway. Uracil is converted to 3-ureidopropionate, which is hydrolyzed by AmaB (β-alanine synthase) to CO 2 , NH 4 + , and β-alanine ( 69 ). S. meliloti 1021, which also lacks PanD but harbors AmaB, should therefore produce β-alanine this way.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in R. etli CFN42, the amaB mutant is auxotrophic for β-alanine ( 69 ), a phenotype that can be explained by the absence of dat and ddc . On the opposite, a S. meliloti 1021 mutant disrupted for amaB ( Smc01820 ) is expected to grow in a minimal medium devoid of β-alanine.…”
Section: Resultsmentioning
confidence: 99%